EFEKTIVITAS TEMEPHOS SEBAGAI LARVASIDA PADA STADIUM PUPA Aedes aegypti - Bhakti Chrisna Pambudi; Martini Martini; Udi Tarwotjo; Retno Hestiningsih (Jurnal Kesehatan Masyarakat (Undip), 2018)
The countermeasures of DHF disease is caused by several factors which is interacted one another. Application of insecticide as larvacide is the most common way to used by society to control vector growth and insecticides are often used in Indonesia is Abate with temephos active ingredient. This research aimed to asses the effect of application larvacide with active ingredient temephos to mortality of Aedes aegypti pupae stadium and survivality imago stadium. The type of this research was an experimental research using post only control group design approach. The population used in this research was Ae. aegypti pupae which was breed in the laboratory. The number of tested pupae used in this research were 25 for every tested medium and conducted for 5 times repeatedly. Therefore, the total of pupa used were 750 larva. The data analysis using the Kruskal wallistest and followed by Mann whitney test.The analysis result showed that there were significant differences between the number of pupae which become imago (p=0.001) and the number of imago which survived until the second week (p=0.001). Death occurs because temephos belongs to organophosphate compounds that have anticholinesterase action.Inhibits cholinesterase enzyme, causing disruption to nerve activity because acetylcholine accumulates on the nerve endings an causes death.